The Effect Of General Allocation Funds (DAU) And Regional Original Revenue (PAD) On Regional Expenditure (Case Study of Districts/Cities in Southeast Sulawesi 2021-2024) - Tandipuang, Anita; Sabandar, Sita Yubelina; Mallisa, Mika (LPPM Universitas Buddhi Dharma, 2025)
This study aims to determine the effect of the General Allocation Fund (DAK) and Regional Own Revenue (PAD) on Regional Expenditure in Regency/City Governments in Southeast Sulawesi. The type of research used in this study is associative/relationship research, which aims to determine the relationship between two or more variables: regional original income and general allocation funds to capital expenditure. The data collection technique used in this study was documentation with secondary data from the Directorate General of Regional Government Financial Balance. The data analysis technique used was quantitative analysis. The data analysis technique used multiple linear regression with SPSS. The results show that PAD (Paid Regional Allocation Fund) and DAU (General Allocation Fund) have a joint and partial effect on Regional Expenditure, meaning that an increase in the General Allocation Fund (DAK) and Regional Original Revenue (PAD) will also affect Regional Expenditure, which will also increase.